BOSHLANG’ICH SINFLARDA MATEMATIKA O’QITISHDA DARSDAN TASHQARI MASHG’ULOTLARNI TASHKIL ETISH METODIKASI - Ibadullayeva Shaxnoza Ibadullayevna (Journal of new century innovations, 2024)
The article discusses the importance of organizing extracurricular activities in order to attract primary school students to the subject of mathematics, to better master the teaching materials and to develop their skills.